SCIENTOMETRIC ANALYSIS OF TRANSPORT PHENOMENON LITERATURE, 1900-2007 - Ming, Yueh Tsay; Yi, Jen Lin (Malaysian Journal of Library and Information Science, 2009)
The present study explores the characteristics of transport phenomenon literature from 1900 to 2007 based on the Science Citation Index Expanded (SCITM Expanded) database and its implication using two scientometric techniques, namely Bradford-Zipf’s law and Lotka’s law. The results of this work reveal that the literature on transport phenomenon grows exponentially with an annual growth rate of about 8.67% for the last century. The document type and language distribution, country and institution productivity, core journals, journals with highly cited documents, most highly cited articles and leading authors on transport phenomenon are identified. The present study indicates that the journal literature on transport phenomenon confirms the typical S shape for the Bradford-Zipf plot. The author productivity distribution however does not confirm with Lotka’s law by the Kolmogorov-Smirnov (K-S) goodness of fit test.